How the Influencer Characteristics Impact Purchase Intentions: The Brand Image Mediation Effect - Alamayreh, Esraa M.; Fadhil, Khalid; Issam, Nash’at (Journal of Posthumanism, 2025)
In this era, influencers have prompted organizations to restructure their marketing strategies through incorporating them as an effective strategy in the marketing campaigns. This study aims to understand how influencers influence purchase intention of customers through exploring the mediating role of brand image between influencer characteristics and customer purchase intention. Using a sample of 281 customers, a quantitative approach was utilized to test the proposed hypotheses. The data collected was analyzed using SEM-PLS. The findings revealed that all the study hypotheses are statistically supported. Specifically, the study showed that influencers positively the purchasing decision of customers and on the brand image. In addition, the study also revealed that brand image plays a mediating role in the relationship between influencers and purchase intentions. Such findings provide valuable insights for decision makers about the importance of influencers in shaping the perception and purchasing decisions of customers.